2006
DOI: 10.1016/j.febslet.2006.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulphoxide as a tool to increase functional expression of heterologously produced GPCRs in mammalian cells

Abstract: High-level overexpression of G protein-coupled receptors GPCRs in mammalian cells remains a difficult task inspite of newly developed virus based expression systems. Here, we show that the functional expression level of the recombinant bradykinin receptor (B 2 R) in mammalian cells can be increased up to sixfold just by the addition of dimethylsulphoxide in the culture medium. Total expression level, cellular localization and binding affinity of the recombinant receptor for its endogenous ligand remains unalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
2
6
1
Order By: Relevance
“…Large‐scale cultures (25 L) were grown using a Wave bioreactor (SYSTEM20/50, WAVE BIOTECH). Membrane preparation and [ 3 H] BK binding experiments were performed as described in references 3335. K d values of 0.4±0.1 n M were obtained and compare favorably to those reported for human decidual cells (0.85 n M ) 50.…”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…Large‐scale cultures (25 L) were grown using a Wave bioreactor (SYSTEM20/50, WAVE BIOTECH). Membrane preparation and [ 3 H] BK binding experiments were performed as described in references 3335. K d values of 0.4±0.1 n M were obtained and compare favorably to those reported for human decidual cells (0.85 n M ) 50.…”
Section: Methodssupporting
confidence: 69%
“…Preparation of human GPCR B 2 R: B 2 R was produced in Sf9 cells using the baculovirus system. Expression constructs and optimized production conditions were reported earlier 3335. Large‐scale cultures (25 L) were grown using a Wave bioreactor (SYSTEM20/50, WAVE BIOTECH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Futhermore, a cooperative effect was observed when a combination of both compounds was added to the medium. When compared to similar studies conducted on several GPCRs with other expression systems, where it was shown that the main effect of these chaperones was to improve the functionality of the expressed receptors (André et al 2006;Shukla et al 2006;Sarramegna et al 2002), our results unexpectedly demonstrated that these molecules also increased the total amount of EGFP-hMOR. Whether this particular feature is related to the S2 cells system alone or is receptor dependent needs to be further investigated.…”
Section: Distribution Of Functional Egfp-hmor Among Subcellular Membrcontrasting
confidence: 71%
“…Optimization of the culture conditions through the addition of additives, such as ligands [65,129] , amino acids [130] , and DMSO [130,131] , and by altering temperature [130] can increase expression by nearly 10 -fold [130] .…”
Section: Factors Infl Uencing Gpcr Overexpressionmentioning
confidence: 99%